Strategies of South African professional firms: An empirically grounded typology - Faith Botha; Mark Orkin (South African Journal of Business Management, 1993)
Professional organizations are facing a number of environmental challenges in South Africa in the 1990s. The options open to them in successfully positioning their organizations in the face of these challenges presented the research problem. Professional organizations were researched from the perspective of integrated archetypes of organizational form, strategy and the perceptions and values of the top management team. The research was conducted on 56 prominent professional organizations from six professions in South Africa, with an inductive research approach being taken. Theory indicated four possible options and three instruments were developed and tested to test the theory among the partners and stakeholders of the firms. Multivariate techniques of factor and cluster analysis were applied to the resulting data, and the findings indicated five broad configurations of adaptation, three of which concurred with the theory, the fourth which was positioned across the boundaries of two of the theoretical options, and the fifth which was positioned along a third dimension to that suggested by the theory, namely, that of the collective values of the top management team. It appeared that a large number of professional organizations in South Africa still operate successfully from the basis of their professional reputation, but that equally, a number have also adopted more innovative approaches.
Keywords: 650